Sinonasal quality of life in patients after an endoscopic endonasal surgery of a sellar tumour - Novák, Vlastimil; Hrabálek, L; Hoza, J; C Hučko; Pohlodek, D; Macura, J (Scientific reports, 2021)
Endoscopic endonasal approach uses the nasal cavity and paranasal sinuses to access the cranial base and may be a source of post-surgical morbidity in many patients with a sellar tumour. The objective of the presented study was to evaluate sinonasal quality of life and assess the effect of chosen reconstruction of the cranial base on the final condition. 65 patients, 33 male and 32 female who underwent an endoscopic endonasal surgery due to sellar expansion, were included into this prospective study. Sinonasal quality of life was evaluated using the Sinonasal Outcome Test-22 (SNOT-22) questionnaire before the surgery and six months after the surgery. Sinonasal quality of life was evaluated for the total cohort of patients and for patients after reconstruction (fascia lata, muscle) and without reconstruction. The minimum follow-up period was one year. There was no significant difference between the score (SNOT-22) before the surgery (average 14.4 points) and after the surgery (average 17.5 points), p = 0.067 in the whole cohort. Statistically significant differences were found in the following items-the need to blow nose, nasal congestion, loss of smell and taste, and thick discharge from the nose. The comparison of subgroups with and without the reconstruction yielded statistically significant differences in favour of patients with reconstruction in the following items-lack of high-quality sleep and feeling exhaustion. The endoscopic endonasal approach in patients with a sellar tumour is a gentle method with minimal effects on sinonasal quality of life over a period longer than six months. The most common complaints are the need to blow nose, nasal congestion, loss of smell and taste, and thick discharge from the nose. Cranial base reconstruction using the muscle and fascia lata seems to be a potential factor positively influencing sinonasal quality of life.
Keywords: paranazální dutiny; následné studie; Endoscopy; lidé; nádory hypofýzy; Adult; Middle Aged; Prognosis; prognóza; Sella Turcica; prospektivní studie; Paranasal Sinuses; Female; nosní dutina; endoskopie; Quality of Life; Humans; Follow-Up Studies; sella turcica; Prospective Studies; Pituitary Neoplasms; lidé středního věku; mužské pohlaví; mladý dospělý; Nasal Cavity; ženské pohlaví; Young Adult; nemoci nosu; kvalita života; Male; Aged; dospělí; Nose Diseases; senioři